2011
DOI: 10.22229/xpw610283
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and Free Association for Multicultural Competence: A Model for Clinical Group Supervision

Abstract: Clinical supervision is a critical process used to foster the development of professional competencies among counselors in training (CITs) in the counseling profession. Despite the significance of clinical supervision, CITs often report nondisclosure; that is, an unwillingness to share certain information regarding their work with a client for fear of negative evaluation from their supervisor. To address this barrier, the authors of this article propose a model integrating mindfulness and free association for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…For example, Goreczny et al (2015) and Kozina et al (2010) showed that as trainees undergo their training experiences, they gain more selfefficacy. Similarly, counselor self-efficacy has been determined to be an important factor to assess in multicultural supervision and counseling, due to varying levels of selfefficacy across people and potentially those from different backgrounds (Lam et al, 2013;Schauss et al, 2017). Toward this end, counselor supervisors work with supervisees to help establish multicultural attitudes, beliefs and skills that will guide them through the beginning stages of their practice, as well as throughout their careers (Fietzer et al, 2018;Morrison & Lent, 2018).…”
Section: Counselor Self-efficacymentioning
confidence: 99%
“…For example, Goreczny et al (2015) and Kozina et al (2010) showed that as trainees undergo their training experiences, they gain more selfefficacy. Similarly, counselor self-efficacy has been determined to be an important factor to assess in multicultural supervision and counseling, due to varying levels of selfefficacy across people and potentially those from different backgrounds (Lam et al, 2013;Schauss et al, 2017). Toward this end, counselor supervisors work with supervisees to help establish multicultural attitudes, beliefs and skills that will guide them through the beginning stages of their practice, as well as throughout their careers (Fietzer et al, 2018;Morrison & Lent, 2018).…”
Section: Counselor Self-efficacymentioning
confidence: 99%